2017
DOI: 10.1080/21645515.2017.1337614
|View full text |Cite
|
Sign up to set email alerts
|

Product review on the monoclonal antibody palivizumab for prevention of respiratory syncytial virus infection

Abstract: Respiratory syncytial virus (RSV) accounts for about 20% of all respiratory infections in children below the age of 5 y. It is associated with up to 63% of all acute respiratory infections and up to 81% of all viral lower respiratory tract infections causing hospitalization in infants and young children. RSV leads to seasonal epidemics between November and April in the northern hemisphere. Most severe infections (RSV accounts for 50 to 80% of all cause bronchiolitis) affect infants younger than 6 months of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
110
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 111 publications
0
110
0
5
Order By: Relevance
“…Overall, there is no vaccine or effective treatment besides supportive measures. Although palivizumab is available for preventing RSV-associated hospitalizations, it is not very cost-effective and is mainly limited to high-risk infants for the first RSV season (7). Here, we identified a new potential role of EPAC molecules in airway epithelial cells in response to RSV infection.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Overall, there is no vaccine or effective treatment besides supportive measures. Although palivizumab is available for preventing RSV-associated hospitalizations, it is not very cost-effective and is mainly limited to high-risk infants for the first RSV season (7). Here, we identified a new potential role of EPAC molecules in airway epithelial cells in response to RSV infection.…”
Section: Discussionmentioning
confidence: 95%
“…It is well known that RSV infection enhances the production of several cytokines/chemokines, including IP-10, RANTES, and MIP-1␤, in airway epithelial cells (16,46,47). The expression of these cytokines/chemokines promotes activation and recruitment of immune cells, resulting in increased secretion of inflammatory cytokines/chemokines (7,10). Several reports have shown that excessive host responses induced by inflammatory mediators may be linked to hyperresponsiveness and airway damage during virus clearance (20,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Causality between early infection and development of asthma has been hard to prove, but perhaps one of the more convincing pieces of evidence involves palivizumab, an anti-RSV antibody that has been shown to have 70%-80% efficacy in preventing RSV hospitalization. 37 Treated patients were followed up to age 6 years. By that time, there was no significant difference in asthma prevalence between treated and untreated groups; however, there was significantly decreased rate of recurrent wheezing in the cohort.…”
Section: Reviewmentioning
confidence: 99%
“…Thirty-three million cases worldwide in children under at age 5 are estimated to be infected with RSV-associated acute lower respiratory infections and about 10% of patients were being hospitalized, resulted in about 1-3% of in-hospital deaths [8]. Palivizumab, the licensed monoclonal antibody (Ab), has been used as a prophylactic drug to prevent severe RSV disease in high-risk children [9]. Since palivizumab has safety and efficacy concerns such as anaphylaxis and hypersensitivity reactions, palivizumab is not recommended for the therapeutic-treatment post-RSV infection [10].…”
Section: Introductionmentioning
confidence: 99%